Circular Economy Goals, Large Capitalisation, and ESG Funds: An Investment Perspective - R. Anvekar; S. Patil (Финансы: теория и практика, 2024)
In the context of an obvious 32% growth, the relationship between the circular economy, risks and returns is becoming increasingly relevant. ESG indicators are increasingly pivotal in global investment decisions. The purpose of the study is to demonstrate that ESG-mandated companies are more likely to yield sustainable long-term performance, advocating for investors to consider ESG-based mutual fund schemes. The research evaluates the performance of the top 10 high-capitalization and ESG equity funds, comparing them to the Nifty-50 benchmark index using various performance metrics. An increasing trend in ESG-compliant investing is observed, contributing to the circular economy. It was concluded that even post-risk adjustment, ESG funds remain lucrative, offering sound long-term returns. Statistically significant returns are noted in both funds and index. The study recommends companies revise policies towards ESG compliance and investors kindness ESG funds. The novelty of the study is that it gives a new insight into the performance of two different categories of funds, how well circular economy strategies can contain investment risk and provide risk-adjusted returns.